2001
DOI: 10.1111/j.1469-7793.2001.0433a.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signalling and PKCα activate increased endothelial permeability by disassembly of VE—cadherin junctions

Abstract: The role of intracellular Ca2+ mobilization in the mechanism of increased endothelial permeability was studied. Human umbilical vein endothelial cells (HUVECs) were exposed to thapsigargin or thrombin at concentrations that resulted in similar increases in intracellular Ca2+ concentration ([Ca2+]i). The rise in [Ca2+]i in both cases was due to release of Ca2+ from intracellular stores and influx of extracellular Ca2+. Both agents decreased endothelial cell monolayer electrical resistance (a measure of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(201 citation statements)
references
References 28 publications
10
188
0
3
Order By: Relevance
“…Inflammatory mediators such as thrombin and histamine induce vascular leakage defined as increased permeability to plasma proteins and other solutes. Many of these inflammatory mediators trigger increased vascular permeability by increasing intracellular calcium concentrations which then mediate cytoskeletal reorganization and disassembly of VE cadherin at the adherens junctions (Sandoval et al, 2001;Tiruppathi et al, 2002;Vanden broucke et al, 2008;Schulz et al, 2008). In accordance with this, we observed increased permeability for albumin when confluent HMVEC-L were cultured on collagen-coated cell culture inserts for 5 days.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Inflammatory mediators such as thrombin and histamine induce vascular leakage defined as increased permeability to plasma proteins and other solutes. Many of these inflammatory mediators trigger increased vascular permeability by increasing intracellular calcium concentrations which then mediate cytoskeletal reorganization and disassembly of VE cadherin at the adherens junctions (Sandoval et al, 2001;Tiruppathi et al, 2002;Vanden broucke et al, 2008;Schulz et al, 2008). In accordance with this, we observed increased permeability for albumin when confluent HMVEC-L were cultured on collagen-coated cell culture inserts for 5 days.…”
Section: Discussionsupporting
confidence: 74%
“…Elevated intracellular calcium concentrations in endothelial cells are known to cause increased vascular permeability (Sandoval et al, 2001;Tiruppathi et al, 2002;Vandenbroucke et al, 2008). We could show that calcium influx also induced shedding of CD146.…”
Section: Influence Of Cd146 Shedding On Vascular Permeabilitysupporting
confidence: 50%
“…Cytoplasmic hemolytic PLY is released during autolysis, such as occurs because of antibiotic treatment (7,8), and subsequently binds to cholesterol in cell membranes, upon which oligomerization and pore formation take place. These pores facilitate increased intracellular Ca 2+ levels (9), which in turn activate mechanisms leading to contraction of endothelial cells (10,11). These pathways include both myosin light chain (MLC)-dependent mechanisms and microtubule depolymerization, the latter of which can cause disassembly of adherens junction proteins, such as vascular endothelial (VE)-cadherin (12).…”
Section: Aggressive Treatment With Antibiotics In Patients Infected Withmentioning
confidence: 99%
“…At each frequency, the difference in magnitude of the reflected signal, as compared to the incident wave, is measured. In cell biology, this technology is better known as bioimpedance and has been successfully applied to monitoring cell membrane conductivity, [11][12][13][14][15] monolayer permeability, [16][17][18][19] morphology, [20][21][22] migration, 23,24 and cellular micromotion. 25 Our goal was to extend the use of bioimpedance measurements in an embodiment of this technology to the label-free, noninvasive monitoring of the cellular consequences of ligandreceptor interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In concurrence with this work, we are investigating the cellular physiological events that manifest themselves in the biophysical parameters that we measure. The literature has revealed that changes in the cell membrane, 11,14,15 in cell-cell junctions, 17,18 in the degree of cellular adhesion, [16][17][18][19]21,23,24,25 and in the state of the actin cytoskeleton 16,19 can all contribute to bioimpedance measurements. Work is progressing to define our biophysical measurements in terms of cellular physiological changes including, but not restricted to, those mentioned above.…”
mentioning
confidence: 99%